Analysis of Factors Affecting Indonesian Natural Rubber Exports - Zayani, Avivatul; M. Taufiq (International Journal of Economics (IJEC), 2024)
The aim of this research is to determine and analyze the short-term and long-term influence of Indonesian natural rubber production variables, international consumption, and international natural rubber prices on Indonesian natural rubber exports. This research was carried out using Time series data for the period 1989-2022 using numerical calculations of research variables using the Error Correction Model (ECM) analysis method assisted by EViews12 software. The population used in this research is information on Indonesian Natural Rubber Exports for 1989-2022. As a result of the analysis and discussion that has been carried out, it can be concluded that: Indonesian Natural Rubber Production has a positive influence in both the long and short term on Indonesian Natural Rubber Exports. International Natural Rubber Consumption in the long term has an insignificant influence with a negative correlation on the volume of Indonesian Natural Rubber Exports. International Natural Rubber Prices in both the long and short term have an insignificant influence with a positive correlation on Indonesian Natural Rubber Exports.